Use Of Liquid Organic Fertilizer Fish Waste And Chicken Manure Fertilizer On The Production Of Pumpkin (Cucurbita Moschata) - Efrida Lubis; Rini , Susanti; Syofia, Irna; Yoga Pradana , Girsang (Publisher Cv. Inara, 2021)
The study was carried out at altitude of ± 27 mdpl using factorial randomized block design (RAK). Firstly, Fish Waste POC (P) with 3 treatment levels, P1 = 20 ml/l water, P2 = 30 ml/l water and P3 = 40 ml/l water. Secondly, Chicken Manure (K) with 3 treatment levels, K1 = 0.75 kg/plot, K2 = 1.5 kg/plot and K3 = 2.25 kg/plot. The observed parameters were fruit length, fruit diameter, number of fruit per plot and fruit weight per plot.Based on the study, it was found that Fish Waste POC did not significantly affect on all the parameters observed. Chicken manure had a significant effect on the observed parameters, fruit length, fruit diameter and fruit weight per plot, while the combination of both treatments showed that there was no significant effect on all observed parameters